Literature Review: Major Depression with Somatic Comorbidities - Andini Yusuf; Muhammad Alim Jaya; Zulfitriani Murfat (Journal La Medihealtico, 2026)
Major depressive disorder (MDD) is a mood disorder often accompanied by somatic symptoms and chronic physical illness. Complaints such as pain, fatigue, insomnia, headaches, and palpitations are often the primary reasons patients seek medical help, often resulting in a delayed diagnosis. This study aims to determine the relationship between major depression and somatic comorbidities based on published research. The method used was a literature review with a narrative review design. Articles were searched in the PubMed and Google Scholar databases using the keywords "major depressive disorder," "major depression," and "somatic comorbidities." A selection process based on inclusion and exclusion criteria yielded 12 articles published between 2016 and 2026. The review results indicate that major depression is significantly associated with somatic symptoms and chronic physical illnesses such as cardiovascular disease, diabetes mellitus, heart failure, migraines, and metabolic disorders. This relationship is bidirectional, with physical illnesses increasing the risk of depression and depression worsening physical conditions. Management of major depression requires a holistic approach through pharmacotherapy, psychotherapy, and optimal management of physical illnesses.